3D modeling framework and investigation of pollutant formation in a condensing gas boiler. (15th September 2021) - Hinrichs, Jörn; Schweitzer-De Bortoli, Stefan; Pitsch, Heinz
Highlights: Development of a 3D modeling framework for condensing gas boilers. Framework was validated with resolved simulations and experimental data. Full-scale 3D-CFD simulation of a commercial condensing gas boiler device. Captured global CO and NOx emissions well compared to measured data. Identified high emission regions due to locally varying flue gas temperatures. Abstract: Condensing gas boilers exhibit complex global flow-field patterns, which lead to noteworthy inhomogeneities of the burnt gas temperature distribution and levels of local pollutant formation in the combustion chamber. To enable numerical simulations of realistic heating systems, a modeling framework was developed. Challenges like high computational times and the combined multi-physics aspects that occur in quite complex geometries were addressed. The flamelet progress variable (FPV) model was applied, which tabulates detailed reaction kinetics as a function of progress variable and enthalpy. As the larger timescales of CO and NO formation inhibit a direct lookup of local CO and NO mass fractions from the chemistry table, the so called NOMANI model was utilized for NO and a rescaling model was applied for CO. All models were validated against resolved simulation results and experimental measurements. The multi-hole burner was modeled as a porous medium, because it was computationally unfeasible to resolve each burner hole. While local gas acceleration and preheating was considered, the exact flame structure as well as the recirculation zone behind the flame front could not be represented. To still capture the burnt gas temperature, the missing heat losses from the recirculation zone were modeled and coupled to the conjugate heat transfer (CHT) model. The modeling framework was applied to a commercial condensing gas boiler device at nominal load utilizing a lean methane-air mixture. The simulation shows reasonable agreement with experimentally measured emission levels and critical regions with CO and NO x emissions twice as high as in other regions were identified. Temperature variations of 200 K in the flue gas throughout the combustion chamber and 450 K in the solid region of the multi-hole burner were found. Based on these results, design aspects are correlated to CO and NO formation and suggestions on possible design modifications are discussed to further reduce pollutant emissions of such condensing gas boilers.